A walk in the clouds - Kamen, Robert Mark.; Miller, Mark, 1925-; Weitzman, Harvey; Netter, Gil.; Zucker, David, 1947-; Zucker, Jerry; Reeves, Keanu; Sánchez-Gijón, Aitana; Quinn, Anthony, 1915-2001.; Giannini, Giancarlo; Jarre, Maurice; Arau, Alfonso; et al. (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2007)
After returning from World War II, a young G.I. finds he has little in common with the wife he left behind. Disillusioned, he heads north to work as a travelling salesman where he meets the daughter of a wealthy vineyard owner. On her way home, she is terrified of what her father will do when he learns she is unmarried and pregnant. The young man gallantly offers to help by posing as her husband for one night, unaware that doing so will change both of their lives forever.
Title from disc surface.
Originally produced as a motion picture in 1995.
"Based on Quattro passi fra le nuvole. Story and screenplay material by Piero Tellini, Cesare Zavattini and Vittorio de Benedetti, by assignment of Massimo Tellini."
Special features include: Theatrical trailer, interactive menus, scene selection.
Music by Maurice Jarre ; costume designer, Judy L. Ruskin ; edited by Don Zimmerman ; production designer, David Gropman ; director of photography, Emmanuel Lubezki.
Keanu Reeves, Aitana Sanchez-Gijon, Anthony Quinn, Giancarlo Giannini.
Keywords: World War, 1939-1945 -- Veterans -- Drama; Feature films; Fathers and daughters -- Drama; Impostors and imposture -- Drama; Romance films; Feature films; Fiction films; Video recordings for the hearing impaired